Response to 'Beyond sustainability: hope in a spiritual revolution?'. Issue 1 (2nd January 2017) - Muers, Rachel
Abstract : This is a reply to: Bathurst, Rachel. 2017. "Beyond sustainability: hope in a spiritual revolution?" Global Discourse . 7 (1): 87–105.http://dx.doi.org/10.1080/23269995.2017.1300410.